THE INTERPERSONAL RELATION AND THE CLASS - Angelica Mihailescu (National Centre for Policy and Evaluation in Education, 2008)
The aim of this article is to show the way in which the concept of interpersonal relations can stimulate the existing links between the culture of the classroom (representing a a field of interaction between individuals who are in a position to handle rights and responsabilities, to cooperate, to overcome tensions, and so on) and that of the wider society. This implies understanding of the civil education class as a social-cultural space in which self image is being developed by comparison with the others'. There are some aspects which may really sustain the practical dimension of the field of civil education: accepting a set of social-cultural norms regarding the attitudes and behaviours widely assumed by the community, rethinking the concept of social status and a much more flexible redistribution of the roles the participants have at the interactions in the class.